2021
DOI: 10.3389/fnins.2021.605887
|View full text |Cite
|
Sign up to set email alerts
|

Monoamine Levels and Parkinson’s Disease Progression: Evidence From a High-Performance Liquid Chromatography Study

Abstract: Parkinson’s disease (PD) is associated with dysfunction of monoamine neurotransmitter systems. We investigated changes in the levels of monoamine and their metabolites in PD patients, together with their association to clinical profiles. PD patients and age-matched control subjects (n = 40 per group) were enrolled. Using high-performance liquid chromatography (HPLC) with an electrochemical detector, levels of monoamines (dopamine, DA; norepinephrine, NE; epinephrine, EPI; and serotonin, 5-HT) were measured in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…In addition to gut microbiome dysbiosis, another possible mechanism linking PD to IBS was dysregulation of neurotransmitters and neurotrophic factors. It is well-known that deficits in dopamine and 5-HT signaling are implicated in the initiation and progression of PD ( 46 , 47 ), but as for IBS, reduced levels of these neurotransmitters could mitigate pathological symptoms like diarrhea, abdominal pain and discomfort and stabilize intestinal permeability ( 48 51 ). Additionally, although decreased netrin-1 concentrations in the brain and gut of PD patients resulted in significant loss of motor function, it provided an obvious alleviation effect on visceral hypersensitivity, a core characteristic in approximately half of patients with IBS ( 52 , 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to gut microbiome dysbiosis, another possible mechanism linking PD to IBS was dysregulation of neurotransmitters and neurotrophic factors. It is well-known that deficits in dopamine and 5-HT signaling are implicated in the initiation and progression of PD ( 46 , 47 ), but as for IBS, reduced levels of these neurotransmitters could mitigate pathological symptoms like diarrhea, abdominal pain and discomfort and stabilize intestinal permeability ( 48 51 ). Additionally, although decreased netrin-1 concentrations in the brain and gut of PD patients resulted in significant loss of motor function, it provided an obvious alleviation effect on visceral hypersensitivity, a core characteristic in approximately half of patients with IBS ( 52 , 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…[ 18 ] It was found that the blood level of norepinephrine in PD patients decreased significantly with the increase of the Hoehn&Yahr stage, suggesting severe disease conditions. [ 19 ] A retrospective study on 1318 patients with PD found that the risk of OH was higher in PD patients with longer disease course, higher Hoehn&Yahr stage, and more severe disease. [ 20 ] However, in this study, we found that there was no obvious correlation between OH and disease course.…”
Section: Discussionmentioning
confidence: 99%
“…On this basis, the istradefylline-induced epigenetic suppression of A 2A receptor upregulation may have interesting implications for the fundamental goals of LD therapy, although many areas remain to be investigated, including PET imaging of dopamine transporters and A 2A receptors in patients with PD receiving long-term istradefylline treatment [24][25][26][27][28][29][30]. If increased A 2A receptor expression in the indirect pathway contributes to the need for progressive increases in LDD, A 2A receptor epigenesis [21] data and the present real-world evidence (RWE) findings may explain the mechanism underpinning this correlation.…”
Section: Discussionmentioning
confidence: 99%